2020
DOI: 10.1108/pijpsm-03-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

Public police’s philanthropy and Twitter communications in Canada

Abstract: PurposePolice services, police associations and police foundations now engage in philanthropy and these efforts are communicated using social media. This paper examines social media framing of the philanthropic and charitable work of police in Canada.Design/methodology/approachDrawing from discourse and semiotic analyses, the authors examined the ways that police communications frame contributions to charity and community’s well-being. Tweets were analyzed for themes, hashtags and images that conveyed the phil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
2
0
1
Order By: Relevance
“…Posts about connections in the community attempt to legitimize police as part of their communities and are bolstered through appeals to police support of charities and protection of and service to youth. Posts promoting charities foster a mutually beneficial relationship as police seek legitimacy through their charitable giving while charities receive additional promotion for fundraising campaigns ( Walby and Gumieny, 2020 ; Walby et al, 2018 ; Luscombe et al, 2018 ). Furthermore, appeals to connections to youth place police in a position of moral authority, indexing these communications to emotions associated with protection of youth.…”
Section: #Ourtown: Police Communicating Communitymentioning
confidence: 99%
“…Posts about connections in the community attempt to legitimize police as part of their communities and are bolstered through appeals to police support of charities and protection of and service to youth. Posts promoting charities foster a mutually beneficial relationship as police seek legitimacy through their charitable giving while charities receive additional promotion for fundraising campaigns ( Walby and Gumieny, 2020 ; Walby et al, 2018 ; Luscombe et al, 2018 ). Furthermore, appeals to connections to youth place police in a position of moral authority, indexing these communications to emotions associated with protection of youth.…”
Section: #Ourtown: Police Communicating Communitymentioning
confidence: 99%
“…Wood (2020) examines the use of memes by public police on social media, finding that police use humor and images of animals to expand their list of followers and to make more affective connections with the public. In Canada, literature to date has similarly observed that police use multiple strategies on Twitter and other social media sites to curate their image and to manage public views of police work (Walby & Joshua, 2021; Walby & Gumieny, 2020; O’Connor, 2017; Schneider, 2016). Public police communicate and create their own images online in part because of ongoing tensions with news media (Duncan & Walby, 2022; Ellis & McGovern, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Existe ciertamente un creciente número de meta-investigaciones publicadas sobre campos diferentes al de la comunicación política, como por ejemplo sobre educación (Rodríguez-Hoyos et al, 2015;Lytras et al, 2018), la construcción de carrera profesional (Gerber & Lynch, 2017) la salud pública (Sinnenberg et al, 2017;Edo-Osagie et al, 2020), la comunicación corporativa de seguridad (Walby & Gumieny, 2020), el aprendizaje de segundas lenguas (Hattem & Lomicka, 2016) y otras áreas específicas, pero hemos hallado muy escasa meta-investigación centrada en la revisión metodológica de investigaciones sobre comunicación política (o incluso institucional) en En el momento actual, los meta-estudios citados más arriba y otros similares, pueden considerarse desactualizados, dada la dependencia de la interfaz API de Twitter, que publicó una versión completamente renovada (V2.0) en mayo de 2022, incluyendo nuevos límites a la construcción muestral automatizada, lo que obliga a revisar cualquier conclusión previa al respecto. Además, por lo general se interesan por comparar los resultados de distintas series de investigaciones, no enfocándose en la cuestión de la comparativa metodológica, como es nuestro caso, por lo que en la práctica no contamos con antecedentes válidos con los que comparar la evolución en el tiempo de los resultados aquí obtenidos.…”
unclassified